2018
DOI: 10.1109/toh.2018.2851511
|View full text |Cite
|
Sign up to set email alerts
|

Combining Full and Partial Haptic Guidance Improves Handwriting Skills Development

Abstract: It has been shown in previous studies that haptic guidance improves the learning outcomes of handwriting motor skills. Full and partial haptic guidance are developed and evaluated in the literature. In this paper, we present two experimental studies to examine whether combining full and partial haptic guidance is more effective for improving handwriting skills than merely full or partial guidance methods. Experiment I, with 22 participants, compares the effectiveness of merely full and partial haptic guidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…1. The reason is that a good use of HF during training can improve skill acquisition [4]- [7]. In this paper we introduce an exploratory work on a portable haptic device designed to offer hand guidance in 3D space.…”
Section: Introductionmentioning
confidence: 99%
“…1. The reason is that a good use of HF during training can improve skill acquisition [4]- [7]. In this paper we introduce an exploratory work on a portable haptic device designed to offer hand guidance in 3D space.…”
Section: Introductionmentioning
confidence: 99%
“…Providing haptic guidance to users can provide benefits for learning [36] and short-term performance (cf. Abbink et al [1]).…”
Section: Haptic Guidancementioning
confidence: 99%
“…Abbink et al [1]). Teranishi et al [36] demonstrate that participants showed improved learning for handwriting skills when receiving guidance through a 3-DOF Phantom Omni device. Mullin et al [25] use a similar device as handwriting aid for rehabilitation.…”
Section: Haptic Guidancementioning
confidence: 99%
“…Haptic sensation can effectively convey information to users whose vision is blocked or overloaded [15], [16]; therefore, it can also be used as the primary means of the human-robot interaction [3]- [6], [17]. In particular, because haptic feedback can provide directional cues, it has been used in several applications where a robot gives directional guidance to a visually impaired pedestrian.…”
Section: A Haptic Robotic Guidementioning
confidence: 99%